Cyber security in the national security & defence sector of Ukraine: todayʼs challenges and ways to avoid possible threats - Proshchyn , Ihor; Shypovskyi , Volodymyr (Social Development and Security, 2020)
Development of strategic communications is necessary for the effective preparation and use of the Armed Forces, for the coordination of actions of state bodies in defence matters, as well as for the purpose of forming and strengthening the confidence of Ukrainian society in the stateʼs military policy. The basic elements of strategic communications of the Ministry of Defence and the Armed Forces are public relations, public relations in the military sphere, public diplomacy, information and psychological operations. In turn, one of the components of the information operations system is cyberspace actions. The strategic importance of actions in cyberspace is due to the fact that cyber threats today, with devastating consequences, pose no less danger than direct military intervention. In 2016, during the Summit of Heads of State and Government of the North Atlantic Treaty Organization, the first ever EU-NATO security cooperation agreement was signed, in particular on hybrid wars and cyberattacks. Cyberspace, along with land, air, sea, and space, has been recognized as a new operational space, and cyber-operations (cyberattacks) are an integral part of the hybrid war. Also, cyber weapons in terms of scale of successors are compared with weapons of mass destruction. In this regard, cyber security is one of the top priorities for the state. The article is devoted to the research of actual problems of providing the cyber security of the Armed Forces units of Ukraine in the current conditions of development of the information society and during hybrid threats from the Russian Federation side. The authors explain the basic concepts and definitions of the scientific field and explain conceptual approaches to cybersecurity and propose some ways to improve the existing cybersecurity mechanism or how to enhance it.